2018
DOI: 10.1016/j.nicl.2017.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of working memory deficits and associations to response inhibition in obsessive compulsive disorder

Abstract: Previous research in patients with obsessive-compulsive disorder (OCD) has indicated performance decrements in working memory (WM) and response inhibition. However, underlying neural mechanisms of WM deficits are not well understood to date, and empirical evidence for a proposed conceptual link to inhibition deficits is missing.We investigated WM performance in a numeric n-back task with four WM load conditions during functional Magnetic Resonance Imaging (fMRI) in 51 patients with OCD and 49 healthy control p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 51 publications
6
47
1
Order By: Relevance
“…Also, it was reported that continuous psychiatric symptoms more than five years give rise to the increased brain activation and abnormal functional connectivity, inducing the poor memory performance. 8 Another interesting finding in our study is that patients with OCD showed increased GM volumes in the Hip and OFC ( Figure 5A). Hippocampal region and OFC play an essential role in memory encoding and retrieval.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…Also, it was reported that continuous psychiatric symptoms more than five years give rise to the increased brain activation and abnormal functional connectivity, inducing the poor memory performance. 8 Another interesting finding in our study is that patients with OCD showed increased GM volumes in the Hip and OFC ( Figure 5A). Hippocampal region and OFC play an essential role in memory encoding and retrieval.…”
supporting
confidence: 57%
“…There are many other studies [ 31 - 35 ] demonstrating that alteration of Cd volume and abnormal functional activation are associated with symptom severity in OCD. Also, it was reported that continuous psychiatric symptoms more than five years give rise to the increased brain activation and abnormal functional connectivity, inducing the poor memory performance [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emotional processing is adaptively modulated by executive control in healthy participants (Iordan, Dolcos, & Dolcos, ; Okon‐Singer, Lichtenstein‐Vidne, & Cohen, ). In accordance with this, several psychological disorders are associated with alterations in executive control functions such as performance monitoring and conflict processing (Endrass & Ullsperger, ; Grützmann et al, ; Moser, Moran, Schroder, Donnellan, & Yeung, ; Proudfit, Inzlicht, & Mennin, ) or working memory (Heinzel et al, ). Executive dysfunction, as indexed by increased error monitoring, is also found in healthy participants with habitually increased negative affect or anxiety (Hajcak, McDonald, & Simons, , ).…”
Section: Discussionmentioning
confidence: 86%